Um olhar para o Programa Acessa Escola: condições dos laboratórios de informática das escolas públicas de Guaratinguetá - Firme, Ingrid Cordeiro [UNESP] (Universidade Estadual Paulista (Unesp), 2013)
Considering the necessity of implementation of the Information Technologies and Communication (ICT) in the public Brazilian schools, the São Paulo State government hearing the call of the federal government and, with the objective to promote the digital inclusion, created the Programa Acessa Escola. The research that we realized and bring expressed on this text, is about such program and allowed us comprehend how it had been developed in the public state schools of the city of Guaratinguetá. By visiting the schools, we saw the manner that each school make use of his informatics laboratory; how they understand the government Project; how they develop actions of use of the laboratory and, particularly, how they use the informatics laboratory to the teaching and learning of mathematics helping the professor and the students. To make possible to understand this use, was realized interviews with the responsible intern of each one of the 14 (fourteen) schools of Guaratinguetá; with the pedagogical coordinator or director of the school and with the mathematics teacher. By the analysis, realized using a qualitative approach of phenomenological nature, we understand that the intern see himself as an auxiliary of the student and professor in the use of the laboratory. The director or pedagogical coordinator understand that the laboratory is an excellent resource to the school, but still exist the necessity of more resources that allow to attend properly the community; and the mathematics teacher consider important the program in the school as much for the students digital inclusion as for the teaching but they feel not safe to use into his classes, because they consider that there is a lack of capacitation and collaboration to make their activities relevant to the learning. That make possible to recognize what is the function of the intern and what is the way that the students and professor ... ( Complete abstract click eletroctronic access below)

Considerando a necessidade de implementação das Tecnologias da Informação e Comunicação (TIC) nas escolas públicas brasileiras, o governo do Estado de São Paulo atende ao apelo do governo federal e, com o intuito de promover a inclusão digital, cria o Programa Acessa Escola. A pesquisa que realizamos, e trazemos expressa neste texto, é sobre tal programa e nos permitiu compreender como ele está sendo desenvolvido nas escolas públicas estaduais do município de Guaratinguetá. Por meio de visitas às escolas vimos de que maneira cada escola faz uso de seu laboratório de informática; como entendem o projeto governamental; como desenvolvem ações de uso do laboratório e, particularmente, como usam o laboratório de informática para o ensino e a aprendizagem da matemática. Para que pudéssemos entender esse uso realizamos entrevistas com o estagiário responsável pelo programa Acessa Escola em cada uma das 14 (quatorze) escolas de Guaratinguetá. Também foram realizadas entrevistas com o coordenador pedagógico da escola (ou o diretor) e com o professor de matemática. A partir das entrevistas, realizada segundo uma abordagem qualitativa de caráter fenomenológico, entende-se que o estagiário se vê como um auxiliar do professor e do aluno no uso do laboratório. O diretor ou coordenador pedagógico entendem que o laboratório é um excelente recurso para a escola, porém destacam que falta infraestrutura para atender adequadamente a comunidade. Da fala do professor de matemática compreende-se que, embora ele considere importante o Programa para a escola e a comunidade, não se sente seguro de utilizar o laboratório nas aulas, pois considera que falta capacitação e colaboração para que as atividades sejam relevantes à aprendizagem
Keywords: Informática na educação; Tecnologia da informação; Fenomenologia; Ensino auxiliado por computador; Phenomenology